The effects of charring on morphology and stable carbon and nitrogen isotope values of common and foxtail millet grains - Teira-Brión, Andrés; Stroud, Elizabeth; Charles, Michael; Bogaard, Amy (Frontiers in Environmental Archaeology, 2024)
Stable isotopes are a core method for assessing crop growing conditions in different climatic and soil environments and, thereby, for understanding past agricultural practices. However, isotopic values in plants are altered depending on distinct forms of preservation, including degrees of charring. To investigate this issue in two cereals, common millet (Panicum miliaceum L.) and foxtail millet [Setaria italica (L.) P.Beauv.], we conducted experimental charring to address key questions in millet agriculture and archaeological grain preservation. The results of the experiment under relevant and controlled conditions of charring establish that the relevant temperatures for well-preserved millets occur between 230°C and 250°C and through short-term exposures of up to 6 h of charring. The data confirm that charring increases δ13CVPDB and δ15NAIR values in both common millet and foxtail millet. Husked grains had consistently lower δ13C values than huskless grains, indicating a differential effect of charring on husks and grains, whereas δ15N values are similar regardless of husks. Stable carbon isotope values are relatively similar in uncharred and charred grains, whereas the effects of charring on stable nitrogen isotope values are greater and need to be taken into account when interpreting the values of archaeological grains and palaeodietary analysis in conjunction with human and faunal values. This study significantly advances the understanding of the isotopic effects on archaeological charred grains of common and foxtail millet within their optimal heating preservation window.